Cardiovascular comorbidity and its impact on patients with COVID-19 - Guan, Wei-jie; Liang, Wen-hua; He, Jian-xing; Zhong, Nan-shan (The European respiratory journal, 2020)
We truly appreciate the comments from C.E. Leiva Sisnieguez and colleagues, who have performed a further analysis on the potential association between cardiovascular comorbidities and the clinical outcomes of coronavirus disease 2019 (COVID-19), particularly the mortality). We also applaud the suggestion to thoroughly adjust for potential confounding factors when interpreting the association between specific categories of cardiovascular comorbidities ( e.g. hypertension) and the clinical outcomes of COVID-19. To this end, we have attempted to incorporate the cardiovascular diseases (including coronary heart disease) into the multivariate regression model [1]. Findings of the model indicated a prominent collinearity between hypertension and coronary heart disease, and we have therefore elected to retain hypertension in the regression model for further analyses. Comorbid hypertension correlates with poorer outcomes in patients with COVID-19 https://bit.ly/2zoT9f0